Acute limb ischemia caused by floating thrombus in the aorta: a case report and literature review - Guo, Fuzheng; He, Zhibin (Frontiers in Cardiovascular Medicine, 2023)
This report presents a patient with rheumatoid arthritis and COVID-19 infection one month earlier who experienced embolic episodes resulting in acute lower-limb ischemia from an unusual source. The blood flow was successfully restored by femoropopliteal thromboembolectomy. In determining the source of the embolism, the patient underwent electrocardiogram, transthoracic echocardiogram, and aortic CTA. The latter revealed a large, pedunculated, and mobile thrombus arising from the aortic arch and the descending thoracic aorta. Considering the patient's general health condition, we performed anticoagulation of the floating thrombus in the aortic lumen. The mechanism of aortic floating thrombosis exhibits considerable complexity. There are no standardized treatment protocols or clinical guidelines, and its treatment mainly includes open surgery, aortic endoluminal stent -graft insertion and pharmacological anticoagulation. Treatment strategy should be based on the cause of the disease and the patient's physical condition.